Pengembangan Mesin Pencacah Tandan Kosong Sawit (TKS) dengan Metode Pemotongan Crusher - Junaidi - -; Anwar Kasim -; Aidil Zamri -; Sir Anderson - (Jurnal Ilmiah Poli Rekayasa, 2014)
Palm empty fruit bunches (EFB) fiber content ± 70 % and can be used for elastic    fiber, matrix, mattresses, rugs and raw material fiber -based composite board products, but until now has not been utilized to the fullest . The problem is not the availability of processing unit generates EFB fiber in small scale . One of them is the processing unit thrasher EFB. EFB counter technology that exists today is a large scale that can only be owned by the oil palm industry with a capacity of ± 4,124 kg/hour. For small-scale fiber industry needs a minimum engine capacity of census enumerators ± 300 kg/hour, but this machine is not yet commercially available.In general, the purpose of this research is small scale EFB cutting machines with a capacity of 200-300 kg/hour, the design parameters and identify optimum operating conditions for each component with the technical test of the prototype. From the results obtained machine design an engine capacity of 300 kg/hour, with a few major components, namely counter unit, unit funnel in and out, frame and drive unit . From the results of design calculations obtained engine power 15 hp motor drive with 1450 RPM rotation with 3 phase. From the results of the testing machine in the first enumeration results obtained by the size of the pieces of shredded EFB ± 7 x 7 ( cm ), while the second enumeration stage shredded EFB size becoming smaller ± 3 x 3 ( cm ).